Platelets as a potential new immune coordinator in T cell-mediated aplastic anemia - Tan, Shuai; He, Huizhen; Li, Yuxin; Shang, Mingyue; Cao, Yaofang; Zou, Dongmei; Hu, Ronghua; Hui, Wuhan; Chang, Xiaoli; Ni, Jing; Ma, Qiang; Su, Li; et al. (Frontiers in Oncology, 2025)
Acquired aplastic anemia (AA) is a bone marrow failure syndrome characterized by pancytopenia and decreased hematopoietic stem and progenitor cells (HSPCs) in the bone marrow, it can be either congenital or acquired, predominantly affecting adolescents and the elderly, with higher incidence in Asia compared to Europe and America. Current treatment options include allogeneic hematopoietic stem cell transplantation or immunosuppressive agents, yet proximately a third of patients fail to reach long-term survival. AA is primarily driven by immune-mediated destruction of HSPCs, initiated by self-activated T cells. Early stages feature a Th1 response, which later shifts to Th17 and effector memory CD8+ T cells. Key cytokines including interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α) play crucial roles in this immune dysregulation, influencing HSPCs and contributing to bone marrow failure. Furthermore, bone marrow macrophages (MΦ), particularly M1 subtype, are implicated in AA via the TNF-α/TNF-α receptor pathway, leading to T cell activating and subsequent HSPC damage. Interestingly, MΦ with high expression of IL-27Ra have been demonstrated to contribute to HSPC destruction in AA murine models. Beyond their role in thrombosis, platelets also participate in immune regulation. Some studies suggest that platelet may modulate T cell responses through mechanisms such as Akt-PGC1α-TFAM pathway or PF4-mediated activity, which could play a role in AA. However, direct evidence connecting platelet regulation to T cell-mediated HSPC damage is limited, and current research has largely focuses on CD8+ T cells. Moving forward, it is essential to investigate the interactions between platelets, CD4+ T cells, and mitochondrial energy metabolism. In this review, we propose that platelet-derived factors such as PF4 and TGFβ may activate mitochondrial pathways, influencing T cell activation and leading to HSPC destruction in AA. This hypothesis could provide new insights into the molecular mechanisms of AA and pave the way for novel therapeutic strategies (Highlight).